The determinant that influencing the performance of Islamic banks in Malaysia - Hairul Anuar, Wan Nur Syafiyyah Asma’ (2022)
In these studies, is to determine the key influencing the performance of Islamic banking in Malaysia by using return on assets (ROA) as the dependent variable. The study focuses on loan loss provision to total assets, net loans to total assets, total overhead cost to total assets, shareholders equity ratio, bank size, gross domestic product (GDP) and inflation. The study’s goal will be to examine the performance of the fifteen (15) Islamic banks in Malaysia that may employ panel specifics in terms of ROA in the period of 2011 to 2020. In fact, our data assessment methodology, as well as all associated material pertinent to this study, such as the annual reports of each of the Islamic banks, DataStream, and EViews, will be implemented in this study. The Pooled Ordinary Least Squares (OLS) Model is used to regress the balanced panel data. The result for this study shows that net loan to total assets, total overhead cost to total assets, shareholders’ equity ratio, bank size, gross domestic (GDP) and inflation have significant relationship with the performance of the Islamic bank in Malaysia.